Effect of ultraviolet light, organic acids, and bacteriophage on Salmonella populations in ground beef. (May 2018) - Yeh, Y.; de Moura, F.H.; Van Den Broek, K.; de Mello, A.S.
Abstract: This study investigated individual and combined effects of organic acids, bacteriophages, and ultraviolet light interventions on Salmonella populations in ground beef. Beef trim was inoculated with four Salmonella strains to result in a contamination level of 3.5 log CFU/g after grinding. Lactic (LA) and peroxyacetic (PAA) acids, bacteriophages (S16 and FO1a) (BA), and ultraviolet light (UV) were applied on fresh trim prior to grinding. Applications of individual or combined organic acids did not significantly decrease Salmonella populations in ground beef. Individual applications of BA and UV light decreased approximately 1 log CFU/g ( P  < 0.05). Combined applications of BA and UV provided an optimal decrease of 2 log CFU/g ( P  < 0.05). Organic acid applications do not reduce Salmonella populations in ground beef when applied on trim prior to grinding. Combined applications of UV and BA may be used in industry settings to improve Salmonella control in ground beef. Highlights: Organic acids including lactic and peroxyacetic do not reduce Salmonella in ground meat. Bacteriophage and UV light individual applications reduced Salmonella in ground beef by 1 log. Combined applications of bacteriophages and UV light reduced Salmonella by 2 log. Combined applications of Bacteriophages and UV light improve Salmonella control in ground beef.